Letter (copy) : Scottish Trade Union food ship - Tewson, Vincent
030-0036-001 International. HVT/EAB/AT/21 11th October, 1938. Mr. Fernandez Shaw, Spanish Commercial Attache, 21 Cavendish Square, London, W.1. Dear Mr. Shaw, SCOTTISH TRADE UNION FOOD SHIP I desire to inform you that arrangements have been made for the shipment of a consignment of food to Valencia. Particulars of the consignment are as follows: 100 tons of Sugar. 70 " Rangoon Beans. 50 " Flour. 25 " (1000 cases) skimmed Condensed Milk. 45 " Dried Fish. 20 " Soap. Dried full cream milk to the value of about £550. The consignment will be conveyed to Valencia by the S.S. Stangate, which is due to leave Glasgow tomorrow, Wednesday, 12th instant. For your information we have consigned the cargo to: Jose Castre, Fondo Internacional de Solidaridad, Bonrepos, Valencia. Yours sincerely, Assistant Secretary. 292/946/30/36